Gastric emptying after treatment of stenosis secondary to duodenal ulceration by proximal gastric vagotomy and duodenoplasty or pyloric dilatation. Issue 9 (September 1978) - White, C M; Harding, L K; Keighley, M R; Dorricott, N J; Alexander-Williams, J
Abstract : A consecutive series of 12 patients with stenosis secondary to duodenal ulceration were treated by proximal gastric vagotomy (PGV) and duodenoplasty or PGV and dilatation of the stenosis. Three months after operation the rate and pattern of gastric emptying of a solid meal was measured in each patient and compared with 18 patients with uncomplicated duodenal ulcer treated by PGV alone. Two patients developed gastric stasis in the early postoperative period which resolved with medical treatment. All patients were asymptomatic and were eating normally three months after operation. There was no significant difference in the rate of gastric emptying postoperatively between the patients who had stenosis and those who had uncomplicated duodenal ulcers. These results indicate that despite early postoperative difficulties in some patients pyloric dilatation or duodenoplasty with PGV are both effective treatments for stenosis due to duodenal ulceration.